Theoretical study on excited-state intermolecular proton transfer reactions of 1H-pyrrolo[3,2-h]quinoline with water and methanol - Nawee Kungwan (2018)
The dynamics of the ultrafast excited-state multiple intermolecular proton transfer (PT) reactions in gas-phase complexes of 1H-pyrrolo[3,2-h]quinoline with water and methanol (PQ(H2O)n and PQ(MeOH)n, where n=1,2)ismodeledusingquantum-chemicalsimulations. The minimum energy ground-state structures of the complexes are determined. Molecular dynamics simulations in the first excited state are employed to determine reaction mechanisms and the time evolution of the PT processes. Excited-state dynamics results for all complexes reveal synchronous excited-state multiple proton transfer via solvent-assisted mechanisms along an intermolecular hydrogen-bonded network. In particular, excited-state double proton transfer is the most effective, occurring with the highest probability in the PQ(MeOH) cluster. The PT character of the reactions is suggested by nonexistence of crossings between ππ* and πσ* states. © Springer-Verlag Berlin Heidelberg 2013.